PERAMALAN PERMINTAAN DAN INVENTORY CONTROL BAHAN BAKU MENU BEVERAGES DI SEECLUES COFFEE MENGGUNAKAN METODE ABC ANALISIS DAN LOT SIZING - Lailatul Meiliya (2023)
In 2019, there were more than 2937 outlets coffee shop circulating in Indonesia. One of the industry coffee shops is Seeclues Coffee. Based on data from the Toffin and Mix magazine survey, it is known that the main reason consumers choose coffee shops is coffee dishes that have a taste with a percentage of 79.35%. Therefore, the owners need to maintain the stability of the quality of taste to grow consumer loyalty by performing inventory forecasting and control of inventory with optimal cost. The aim of this study is to perform control of raw material supplies with optimal cost using comparison of lot sizing techniques method of Material Requirement Planning. (MRP). The MRP calculation of the lot sizing technique is done using data from the results of the demand forecast. In determining the focus of the control of the inventory of raw materials Seeclues Coffee carried out the ABC classification analysis and obtained the results of class A raw materials, namely Pasteurized Milk, Beans Espresso (Blend), Beans Manual, and Lychee Syrup. His best prediction calculation method is Moving Average length 2 with MAPE value on pasteurized milk raw materials of 24,418%, Espresso Beans (Blend) of 26,803%, Manual Beans of 18,415%, and Lychee Syrup of 26,913% which belongs to the category of predictability is quite good and good. The lot sizing calculation using the MRP selected is Lot for Lot with the total cost of inventory on Pasteurized Milk raw materials of Rp316.074,50; Espresso Beans (Blend) of Rp6.844,08; Manual Beans of Rp6,844,08, and Lychee Syrup of Rp131,500,40.